Design of a Cricket Dryer Using PID Control - Vidya Ikawati; Heri Siskandar; Mudofar Baehaqi (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2022)
Cricket drying is an important process in the production of animal feed and the rearing of certain animals. Dried crickets have a longer shelf life, more stable nutritional content, and a lower risk of contamination. Therefore, the use of an efficient and controlled cricket dryer is important to achieve optimal results. The main objective of the design of a cricket dryer with PID control is to create a system that can adjust the drying temperature automatically. With this control system, it is expected to be able to overcome the problem of the drying process which is constrained by weather factors. The PID controller (from the English abbreviation: Proportional–Integral–Derivative controller) is a feedback mechanism controller that is usually used in industrial control systems. The control system is an inseparable part of processes in the field of industrial engineering, because with the help of control systems, desired results can be realized. The control system is needed to improve the response of the dynamic system so that the output signal is obtained as desired. A good control system has a good response to various input signals. Tools made with this system can dry raw materials with low moisture content, so that the dried raw materials can be directly processed into other forms, and the production process is not hampered by a shortage of raw materials. This tool is capable of producing temperatures up to 100 degrees Celsius. A timer relay is also included to regulate the length of the drying process so that quality raw materials are obtained.